The Relationship between Child Rearing Attitudes and Maternal Attachment Styles - OYTUN, Musa (2019)
In this study, the relationship between mothers' attachment styles and child rearing attitudes were investigated. Within the scope of the research, 100 participants filled out maternal adult attachment styles and surveys. In order to measure the research variables, “Demographic Information Form”, “ Experiences in Close Relationships Inventory” and “Child Rearing Attitudes Scale ölç were used. In the scope of the research, firstly, the differences of the scores regarding research variables in terms of demographic variables were examined. In addition, a correlation analysis was conducted between the subscales that measured the research variables. According to the findings of the study, mothers' attachment styles differ significantly in terms of income level. Besides, child development attitudes were significantly different in terms of demographic variables. There was a significant difference in child rearing attitudes in terms of education level, income level and number of children. According to the results of correlation analysis, there was a positive correlation between anxious attachment subscale and authoritarian attitude. The findings of the study are thought to be important in terms of providing information about the psychosocial status of the mother who is a leading figure in child development and providing care for the mothers who are pioneers in care and in light of the studies to be carried out in the further research.